Success Factors from Dutch Agricultural Cooperatives and Canadian Agricultural Cooperatives in the Food and Beverage Sector: A Comparative Analysis - Dodsworth, Arthur A.; Charlebois, Sylvain (Journal of Agricultural Studies, 2021)
Dutch agricultural cooperatives have long been successful in their business growth throughout Europe. With more farmers forming cooperatives that supply locally produced food and beverage products into national and international markets, there is no question that the Dutch are successful at forming agricultural cooperatives. The use of vertical coordination throughout their supply chains combined with the country’s geography provides the opportune place for food and beverage production. However, there is no standard set of ideals or factors that these cooperatives have followed to gain their success. In Canada, more cooperatives exist, but a lack of acceptance of new technologies over the past 20 years has led to a lag in automation and a reliance on labour. While outdated reports exist on starting an agricultural cooperative in Canada, there are still no updated reports that farmers could follow on a national or local scale. A lack of support from the Canadian Government has meant a monopolized cooperative arrangement with Saputo and Agropur being the two primary agricultural cooperatives nationally. The results indicate that there are commonly agreed upon ‘success factors’ and ‘bottlenecks’ among researchers in the Netherlands, over a span of 25 years of research. In Canada, the federal Government conducted interviews with industry and farmers on support for cooperatives across Canada, but little came out of these meetings. These results suggest that additional support for cooperatives in Canada is needed, and while Dutch researchers’ ‘success factors’ were found, they cannot be directly applied to Canadian cooperatives because of policy and geography differences.